Response of Chlorella Sp. to Nickel Pollution - Shakya, Pawan Raj; Kaplan, D (Tribhuvan University Journal, 2010)
Unicellular green microalgae are widely used these days for removing toxic heavy metals from the contaminated environment by virtue of their metal binding capacities confirming resistance mechanisms. Besides, they have several advantages over conventional physico-chemical methods such as ion exchange, precipitation with CaCO3, adsorption, flocculation, etc. The present study is a preliminary investigation regarding an attempt to provide low cost, efficient and an emerging eco-friendly technology for the removal of nickel from the nickel polluted environemtn by the use of (WT) Chlorella sp. and one of the isolated cell lines, EMS-10 of the same species. Growth experiments show the effect of increasing NI2+ concentration on the WT and EMS-10 cultures. However, the ID50 value of the EMS-10 revealed some degree of resistance to nickel. Kinetic experiments reveal effective metal binding capacity in EMS-10 and demonstrated appreciable resistance in response to the nickel toxicity as compared to the WT. Key words: Green microalgae; Physico-chemical methods; EMS-10 Tribhuvan University Journal Vol. XXV, No. 1, 2005 Page:129-139 Uploaded date: 26, September, 2010